EFEK HIPOGLIKEMIK KOMBINASI EKSTRAK LARUT ETANOL DAUN MIMBA (Azadirachta indica A. Juss.) DAN DAUN SAMBUNG NYAWA (Gynura procumbens (Lour.) Merr. TERSTANDAR RUTIN DAN KUERSETIN PADA TIKUS DIABETES TERINDUKSI ALOKSAN - , Anggit L. Sunarwidhi; , Prof. Dr. Agung Endro Nugroho, M. Si., Apt. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Diabetes mellitus is a worldwide major health problem. WHO estimated that more than 220 million people worldwide have diabetes and this number is likely to double by 2030. Exploration of plant combinations could be an alternative for diabetes treatment. Azadirachta indica A. Juss. and Gynura procumbens (Lour.) Merr. are reported to have antidiabetes properties. The aim of this study is to evaluate the hypoglycemic effect of combination of A. indica and G. procumbens ethanolic extract in alloxan-induced diabetic rats. Both plants were macerated with ethanol 70%. Determination of rutin in A. indica and quercetin in G. procumbens was performed by TLC-densitometry. Hyperglycemia in rats was induced by alloxan 150 mg/kgBW. The rats were treated with 3 types of combinations for 15 days. Hypoglycemic effect was evaluated by estimating the blood glucose levels and the rats pancreas histopathology study. A. indica contains 2,86±0,15% rutin and G. procumbens contains 18,86±0,86% quercetin. Combination at the ratio of 50mg/kgBW A.indica:112,5mg/kgBW G.procumbens showed the highest hypoglycemic effect: 68,7412±4,8317% (preprandial) and 73,9072±3,1822% (postprandial). Histopathology studies indicated that this combination improved the morfology and ultrastructure changes of the islets and β cells. It also increased insulin productions and decreased the elevated glucose concentrations. It can be concluded that its hypoglycemic effect was better than that of single treatment of A. indica or G. procumbens. That combination is also potential to be developed as a blood glucose-lowering agent for diabetic patients.